Hotel CSR and job satisfaction: A chaordic perspective - Farmaki, Anna; Pappas, Nikolas; Kvasova, Olga; Stergiou, Dimitrios P. (My University, 2022)
Whilst job satisfaction has been extensively investigated as a CSR moderator or outcome, pertinent literature is predominantly silent on the complexity surrounding the formulation of the construct. This study adopts the theory of complexity and examines the combinations of factors leading to hotel employee job satisfaction within a CSR context. Using fuzzy-set Qualitative Comparative Analysis (fsQCA), those factorial combinations that are significant in driving job satisfaction were first identified, whereas semi-structured interviews revealed the relationships that describe such configurations. Necessary Condition Analysis (NCA) was used as complementary to estimate the effects of size of the examined conditions. In total, three solutions were generated: (i) ethical issues and morality; (ii) hotel-related aspects; (iii) employee-related aspects which are supported by the qualitative data. Results indicate that job satisfaction can be stimulated by diverse combinations of hotel employees’ CSR perceptions, moral identity, subjective norms and work engagement, yielding significant theoretical and managerial implications.
Keywords: CSR perceptions; Employee engagement; hotel Employees; Job satisfaction; Moral identity; Subjective norms